2021
DOI: 10.1029/2021gl093794
|View full text |Cite
|
Sign up to set email alerts
|

Four‐Dimensional Wind Fields From Geostationary Hyperspectral Infrared Sounder Radiance Measurements With High Temporal Resolution

Abstract: Accurate four-dimensional (4D) wind observations are important contributors to atmospheric observation system and numerical weather predictions (NWP). With the help of geostationary meteorological satellites, algorithms to retrieve atmospheric motion vectors (AMVs) from continuous observations have been developed and optimized (Velden et al., 2005). The traditional methodologies are based on feature detection and tracking from three consecutive images. In cloudy skies, the visible and longwave infrared (IR) ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…It should be noted that the GIIRS measurements used in this study come directly from the China Meteorological Administration, while those used by Ma et al (2021) were re-calibrated at Cooperative Institute for Meteorological Satellite Studies. Also, additional observations on July 11 are used here but were not used in Ma et al (2021).…”
Section: Impact Of Sounder Sub-footprint Cloud Information On 3d Hori...mentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the GIIRS measurements used in this study come directly from the China Meteorological Administration, while those used by Ma et al (2021) were re-calibrated at Cooperative Institute for Meteorological Satellite Studies. Also, additional observations on July 11 are used here but were not used in Ma et al (2021).…”
Section: Impact Of Sounder Sub-footprint Cloud Information On 3d Hori...mentioning
confidence: 99%
“…GeoHIS provides a good opportunity for deriving atmospheric 3D horizontal wind continuously over tropical and middle-latitude regions. For example, using 15-min interval Geostationary Interferometric Infrared Sounder (GIIRS) data from FengYun-4A (FY-4A), the first and the experimental satellite of FengYun-4 series (Yang et al, 2017), Ma et al (2021) has demonstrated that higher temporal resolution provides better 3D horizontal winds during Typhoon Maria (2018). The potential of atmospheric 3D horizontal wind with reasonable accuracy from GIIRS under clear skies is evident.…”
mentioning
confidence: 99%
“…The China Meteorological Administration (CMA) launched the Geostationary Interferometric Infrared Sounder (GIIRS) on board the FY-4A on 1 May 2018. The value of these new type of high temporal observations to improve the quality of atmospheric wind profiles and the forecast of track and intensity of tropical cyclones has been recently demonstrated [9][10][11][12][13][14]. EUMETSAT is planning to launch the IRS onboard the MTG-S satellite towards the end of 2023 [15][16][17][18][19].…”
Section: Examples Of Such Instruments Are the National Aeronautics Andmentioning
confidence: 99%
“…(2021) have demonstrated that higher temporal resolution provides better impact on tropical cyclone forecasts with a 4DVAR assimilation system in a global NWP model; Ma et al. (2021) developed novel methodologies for extracting 4D horizontal wind fields from high temporal GIIRS water vapor radiances under clear skies and some cloudy situations, and demonstrated that higher temporal resolution (e.g., 15 min vs. 30 min) provides better 4D wind retrievals.…”
Section: Introductionmentioning
confidence: 99%
“…can provide both thermodynamic and dynamic information for various applications. For example, using measurements from the Geosynchronous Interferometric Infrared Sounder (GIIRS), the first geostationary hyperspectral IR sounder (Yang et al, 2017), Yin et al (2021) have demonstrated that higher temporal resolution provides better impact on tropical cyclone forecasts with a 4DVAR assimilation system in a global NWP model; Ma et al (2021) developed novel methodologies for extracting 4D horizontal wind fields from high temporal GIIRS water vapor radiances under clear skies and some cloudy situations, and demonstrated that higher temporal resolution (e.g., 15 min vs. 30 min) provides better 4D wind retrievals.…”
mentioning
confidence: 99%